Independent Evaluation of IFC’s Development Results 2008 : IFC’s Additionality in Supporting Private Sector Development - World Bank (Washington, DC, 2012)
This year's annual Independent Evaluation of International Finance Corporation's (IFC's) Development Results (IEDR) reviews the development results related to 174 IFC-supported investment operations that reached early operating maturity during 2005-07. It also reviews, for the first time, preliminary results for IFC advisory services based on a pilot that evaluated 293 operations completed during 2004-06. As a second theme, the report provides a first ex-post look at the "additionality" (or unique role and contribution) of IFC's operations.